2007 International Conference on Clean Electrical Power 2007
DOI: 10.1109/iccep.2007.384312
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Global Solar Radiation over Rwanda

Abstract: This paper aims to estimating the global solar radiation in Rwanda. We mainly treated the particular case of Kigali where meteorological data records (sunshine duration, temperature, pressure and humidity) over a period of 20 years (1974 to 1993) are available. As solar radiation data are not available in Rwanda, meteorological models (MRM) were applied and sunshine duration measurements played a particular role. The MRM basedresults were validated by satellite datasets measurements done over a 10-year period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Another academic assessment, undertaken in partnership with the MININFRA Department of Meteorology in 2007, used a meteorological data set to estimate monthly averaged global solar radiation. This was found to vary between 4.3 and 5.2 kWh per meter squared per day over all regions of Rwanda [13], [14] It is planned that about 1.2 million households located far away from the national grid will be facilitated to access electricity through solar PV installations [2]. As for grid connected systems, two solar PV based power plants, one of 250 kW and the other of 8.5 MW, were connected to the national grid by the end of 2014.…”
Section: B Potential Energy Resources Tracking Toward the Futurementioning
confidence: 95%
“…Another academic assessment, undertaken in partnership with the MININFRA Department of Meteorology in 2007, used a meteorological data set to estimate monthly averaged global solar radiation. This was found to vary between 4.3 and 5.2 kWh per meter squared per day over all regions of Rwanda [13], [14] It is planned that about 1.2 million households located far away from the national grid will be facilitated to access electricity through solar PV installations [2]. As for grid connected systems, two solar PV based power plants, one of 250 kW and the other of 8.5 MW, were connected to the national grid by the end of 2014.…”
Section: B Potential Energy Resources Tracking Toward the Futurementioning
confidence: 95%
“…In cooperation with the MININFRA Department of Meteorology, the approximate mean monthly solar irradiance ranges from 4.3 to 5.2 kWh per square meter per day across all regions of Rwanda though remains mostly unexploited [41,42]. The data collected showed that the minimum value of global solar radiation for the Kigali station (R G = 4942 Wh/m 2 /day, R G = 4960 Wh/m 2 /day) arises in May, while the maximum value (R G = 5721/m 2 /day, R G = 5738 Wh/m 2 /day) occurs in May, based on research carried out in the global solar radiation estimation in Rwanda [42].…”
Section: Potential Of Solar Energy In Rwandamentioning
confidence: 99%
“…Even though the country is located in the sub-Saharan region where the rainy season lasts approximately half of the year, average daily solar irradiation is between 4.3 and 5.2 kWh/m2/day. However, PV suitability -also taking slope and vegetation into account -varies significantly across the different regions, with the country's eastern province the most promising for PV (Museruka & Mutabazi, 2007).…”
Section: Inception Of the Projectmentioning
confidence: 99%